Wykonaj mnożenie i zredukuj wyrazy podobne:

( 3x -2)( 4x + 5)

(-2x + 4)(6x - 8)

(-6x -9)(2x +3) rt

(x-7)(-x -5)

(2x - 3) (x2- 3x +7)

(4x +3)(-2x2- 3x +1)

(12x -3)(2x -5)

(0,3x - 1,1)(0,2x - 0,6).



Odpowiedź :

[tex]a)\\\\(3x-2)(4x+5)=12x^2+15x-8x-10=12x^2+7x-10\\\\b)\\\\(-2x+4)(6x-8)=-12x^2+16x+24x-32=-12x^2+40x-32\\\\c)\\\\(-6x-9)(2x+3)=-12x^2-18x-18x-27=-12x^2-36x-27\\\\d)\\\\(x-7)(-x-5)=-x^2-5x+7x+35=-x^2+2x+35\\\\e)\\\\(2x-3)(x^2-3x+7)=2x^3-6x^2+14x-3x^2+9x-21=2x^3-9x^2+23x-21\\\\[/tex]

[tex]f)\\\\(4x+3)(-2x^2-3x+1)=-8x^3-12x^2+4x-6x^2-9x+3=-8x^3-18x^2-5x+3\\\\g)\\\\(12x-3)(2x-5)=24x^2-60x-6x+15=24x^2-66x+15\\\\h)\\\\(0.3x-1.1)(0.2x-0.6)=0.06x^2-0.18x-0.22x+0.66=0.06x^2-0.4x+0.66[/tex]